(untitled) (diségno, 2022)
The use of ephemeral architecture for celebrations and religious events, the first examples of which appear in the 15th century in and around Rome, reached its peak during the Baroque period, spreading to different areas of the Italian peninsula. Artists, set designers and architects invited to create triumphal arches, portals, carousels, and scenography had the opportunity to experiment and study design solutions that they would apply in their artistic and architectural works. [read more]